2020
DOI: 10.1101/2020.11.10.20229435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychometric properties and factor invariance for the General Health Questionnaire (GHQ-28): study in Peruvian population exposed to the COVID-19 pandemic

Abstract: Large-scale epidemics are known to significantly disrupt the mental health and perceived well-being of most populations. In spite of the wide range of screening tools, there are not many reliable and widespread tools for the identification of psychological symptoms in non-clinical populations during a health crisis.ObjectiveThe aim of this study was to conduct a psychometric analysis of the Goldberg’s GHQ-28 (1) through a sample of Peruvian adults using confirmatory factor analysis.Materials and methods434 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Higher scores indicate worse health. Various studies have confirmed the validity and reliability of this tool, with Cronbach's α more than 0.83 ( Ames-Guerreroa, 2021 ).…”
Section: Methodsmentioning
confidence: 84%
“…Higher scores indicate worse health. Various studies have confirmed the validity and reliability of this tool, with Cronbach's α more than 0.83 ( Ames-Guerreroa, 2021 ).…”
Section: Methodsmentioning
confidence: 84%
“…2017), and the general population (Ames‐Guerrero et al. 2020). In the scoring system provided by Goldberg, a minimum of 0 and a maximum of 28 points can be obtained from the scale; higher scores indicate a higher possibility of a mental health disorder (Kılıç, 1996, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Para el GHQ-28 se ha encontrado un alfa de Cronbach entre 0,829 (18) y 0,955 (19); y las siguientes estructuras de 3 o 4 factores: a) Ansioso-somático, disfunción social y depresión (19). b) Depresión severa, ansiedad/insomnio, síntomas somáticos y disfunción social (18,20). c) Depresión severa, disturbios del sueño, síntomas somáticos y disfunción social (21).…”
Section: General Health Questionnaire (Ghq)unclassified